THE GEORGIAN ORTHODOX CHURCH IN CURRENT GEORGIAN POLICY - CHEDIA, Beka (CENTRAL ASIA AND THE CAUCASUS, 2009)
For historical reasons the Georgian Orthodox Church (GOC) has always been a subject of Georgian policy despite its separation from the state registered in the country’s Constitution. At all times religion not only confirmed and preserved the nation’s spiritual values—it served the national and state interests. Today, rapidly unfolding globalization has posed the question of the future role of the church and religious values in general. This is especially important in Georgia where the Christian faith has been and remains one of the components of national self-awareness. “Language-Motherland-Religion” is the linchpin of the national ideology that was revived when the country restored its independence. In the years of Soviet occupation, the Communists either destroyed churches or used them for different purposes (they were turned into clubs, theaters, or storage facilities). In the very early years of Soviet occupation, a Council of Militant Atheists was set up to carry out anti-religious propaganda based on Lenin’s ideas.